The new Ukrainian Autocephalous Church and its image in the ecumenical space - Morariu, Maxim (HTS teologiese studies, 2020)
An important moment in the recent history of the Eastern Orthodox Church was for sure the recognition granted to the Ukrainian Orthodoxy by the Ecumenical Patriarchate of Constantinople with the Tomos of autocephaly (2019). Praised by some Orthodox churches and damned by other, it was preceded by some attempts of negotiation initiated by the Ecumenical Patriarchate and by a few meetings between the representatives of the aforementioned institution, Russian Patriarchate and the Ukrainian local churches that was later recognised by Constantinople and by a Schism between the Constantinople and Moscow. At the same time, it divided the local Orthodox churches between the ones who sustain one or the other side or prefer to remain in a neutral state and determined later meetings like the one from Amman in Jordan (2020), between leaders and representatives of the Orthodox Church. Conscious of the relevance of the event and its potential consequences, we have tried here to see how it was reflected in the ecumenical space. Therefore, we have proceeded to the investigation of the journals from the ecumenical area that spoke about it, and we analysed the way how they saw it and emphasised the main elements that have raised their interest. Together with the ecclesiastical challenges, we found that they were also interested in this problem not only for its theological meaning but also because of its geopolitical relevance. The research, based on the literature investigated, therefore presents the Ukrainian problem and its image in the ecumenical space.Contribution: The research investigates how the image of the Eastern Orthodox Church changed in the ecumenical space after the foundation of the New Ukrainian Church and the debates that followed inside of the Orthodox space in this context. It is linked with the scope of the journal due to the fact that investigates a topic relevant for the ecumenical area and presents a topic that can contribute in the future to the change of the relationships with different churches with the Orthodox one.